2015
DOI: 10.5606/archrheumatol.2015.4454
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Psoriatic Arthritis in Patients With Psoriasis in a Tertiary Hospital

Abstract: Objectives:This study aims to investigate psoriatic arthritis (PsA) prevalence in patients with psoriasis (Ps), and compare clinical and laboratory characteristics of patients with or without PsA. Patients and methods: A total of 126 patients (59 males, 67 females; mean age 45.6±13.8 years; range 18 to 82 years) with Ps who applied to Dermatology Outpatient Clinic between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is reported that arthritis may develop in 13–71% of patients before the emergence of skin lesions even though in most patients, arthritis develops after psoriasis skin lesions occur [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that arthritis may develop in 13–71% of patients before the emergence of skin lesions even though in most patients, arthritis develops after psoriasis skin lesions occur [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic arthritis is an inflammatory arthritis that can occur both in the peripheral joints and axial skeleton and is seen in 6–42% of psoriasis patients that have a negative rheumatoid factor [ 5 , 6 ]. It is reported that arthritis may develop in 13–71% of patients before the emergence of skin lesions even though in most patients, arthritis develops after psoriasis skin lesions occur [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 29 articles included in our final analysis, three studies assessed the extent of skin disease in Pso-PsA patients and the later development of PsA (PASI n = 2, affected sites n = 1). The other 26 studies reported psoriasis severity and the presence of PsA in Pso-PsA and PsA patients: either seven studies, selection bias could have been introduced by patient selection (Choi et al [13]; Cinar et al [14]; Haroon et al [15]; Henes et al [16]; Jamshidi et al [17]; Leijten et al [18]; Truong et al [19]), as they assessed previously undiagnosed PsA in cohorts of psoriasis patients (online suppl. Table S3: detailed study characteristics).…”
Section: Search Resultsmentioning
confidence: 99%
“…Concerning studies that investigated psoriasis severity and the presence of PsA, the overall quality was low. In seven studies, selection bias could have been introduced by patient selection (Choi et al [ 13 ]; Cinar et al [ 14 ]; Haroon et al [ 15 ]; Henes et al [ 16 ]; Jamshidi et al [ 17 ]; Leijten et al [ 18 ]; Truong et al [ 19 ]), as they assessed previously undiagnosed PsA in cohorts of psoriasis patients (online suppl. Table S3 : detailed study characteristics).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Henes et al [ 24 ] documented a 30% prevalence of PsA in 404 patients with psoriasis in Germany (multicenter study). In a similar Turkish hospital-based study, 32 patients (25.4%) out of 126 psoriasis patients had PsA [ 25 ]. Moreover, Ranza et al [ 26 ] reported a prevalence of 33% of PsA in a large number of Brazilian psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%